Preparation method of environment-friendly anhydrous stemming
By using mesoporous alumina and glucose as binding agents, the problem of harmful gases and smoke produced by traditional anhydrous gun clay at high temperatures is solved, and its compressive strength and resistance to slag iron erosion are improved, achieving a more environmentally friendly and efficient preparation of water-free gun mud.
Patent Information
- Application Number
- CN202411888254.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The combination agent of traditional water-anhydrous cannon mud is rich in coal tar and asphalt, which leads to the production of harmful gases and smoke at high temperatures, pollutes the environment, and has weak resistance to slag iron erosion at high temperatures, resulting in a shortened service life and an increase in maintenance costs.
Mesoporous alumina and glucose are used as binding agents. By adsorbing and fixing glucose molecules, mesoporous alumina promotes the bonding strength and reliability with other raw materials, reduces apparent porosity and improves compressive strength.
It effectively reduces the apparent porosity of anhydrous gun clay, improves its high-temperature compressive strength, enhances resistance to slag iron erosion, improves volume stability, and reduces cracking and spalling caused by temperature changes.
Smart Images

Figure CN119330692A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a method for preparing environmentally friendly anhydrous taphole clay. Background Art
[0002] At present, taphole clay can be divided into two categories: water-based taphole clay and anhydrous taphole clay. The former is used in small and medium-sized blast furnaces with low top pressure and low degree of intensive smelting, while the latter is mostly used in large and medium-sized blast furnaces with high top pressure and high degree of intensive smelting. With the development and progress of society, the large-scale and highly weathered blast furnaces and the discharge of a large amount of slag iron have put higher and higher requirements on the performance of the taphole clay, especially the anhydrous taphole clay.
[0003] Traditional anhydrous taphole mud binders are rich in coal tar and asphalt, and both coal tar and asphalt are complex polycyclic aromatic hydrocarbons. They have excellent plasticity and durability, but they emit acidic, spicy, smelly gases and yellow smoke at high temperatures, polluting the environment. When 10% to 15% coal tar is added to the anhydrous taphole mud, its benzopyrene content reaches more than 7000ppm. As we all know, benzopyrene is one of the world's recognized carcinogens and seriously threatens human health.
[0004] In order to be more environmentally friendly, glucose is used as a binder in the prior art to prepare anhydrous taphole mud. However, due to the relatively mild chemical properties of glucose, its ability to resist slag iron erosion at high temperatures is weak, resulting in anhydrous taphole mud being easily corroded by slag iron during use, shortening the service life of anhydrous taphole mud and increasing maintenance costs; during the sintering process, glucose releases water vapor and carbon dioxide, resulting in an increase in apparent porosity, and its weakening effect on mechanical properties is enhanced, resulting in a decrease in the high-temperature compressive strength of anhydrous taphole mud. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a method for preparing environmentally friendly anhydrous cannon clay, which ensures that it is more environmentally friendly while reducing the apparent porosity and improving the compressive strength of the prepared anhydrous cannon clay.
[0006] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a method for preparing environmentally friendly anhydrous taphole mud, comprising the following steps: S1. Add 28-35 parts of brown corundum, 35-40 parts of bauxite, 11-15 parts of clay, 5-8 parts of kyanite, 7-10 parts of ferrosilicon nitride, 14-20 parts of silicon carbide, 9-13 parts of sericite, 10-12 parts of NS-FH composite sintering aid and 6-8 parts of mesoporous alumina into a mixer, stir to obtain a first mixture; S2, adding 12-16 parts of a binder by weight to the first mixture obtained in S1, continuing to stir and mix, to obtain a second mixture; the binder comprises glucose and glycerol, and the mass ratio of the two is (3-4):1; S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0007] Furthermore, the preparation method of the mesoporous alumina is as follows: A1. Weigh 18.2 g of template CTAB, add it into a three-necked flask filled with 150 mL of deionized water, and stir to dissolve the template CTAB in the deionized water to obtain a first solution; A2, weigh 120.75 g of aluminum chloride, add 100 mL of deionized water to dissolve it, obtain a second solution, and add the second solution dropwise into the first solution obtained in A1 to obtain a first mixed solution; A3, weigh 22.5 g of urea, add 50 mL of deionized water to dissolve it, obtain a third solution, and add the third solution dropwise to the first mixed solution obtained in A2 to obtain a second mixed solution; A4. The second mixed liquid obtained in A3 is stirred and then dried. The obtained solid is ground and placed in a muffle furnace and calcined in an air atmosphere to obtain mesoporous alumina.
[0008] Furthermore, in A1, the specific operation of stirring is: stirring at a temperature of 35-38° C. and a stirring speed of 200-220 r / min for 33-35 min.
[0009] Furthermore, in A4, the specific operation of stirring is: stirring at a temperature of 70-73° C. and a stirring speed of 200-220 r / min for 24-26 hours.
[0010] Furthermore, in A4, the specific operation of drying is: drying in a drying oven at 60-65° C. for 2-3 hours.
[0011] Furthermore, in A4, the roasting process includes two stages. In the first stage, the temperature is raised to 400°C at a heating rate of 2-4°C / min and maintained for 3-4 hours; in the second stage, the temperature is raised to 600°C at a heating rate of 1-2°C / min and maintained for 4-5 hours.
[0012] Furthermore, the bauxite consists of coarse bauxite and fine bauxite, the particle size of the coarse bauxite is 3-5 mm, the particle size of the fine bauxite is 0.1-1.1 mm, and the mass ratio of the coarse bauxite to the fine bauxite is 1:(1-2).
[0013] Furthermore, the particle size of the sericite is 0.066-0.074 mm, the particle size of the brown corundum is 0.27-0.35 mm, the particle size of the clay is 0.074-0.085 mm, the particle size of the kyanite is 0.24-0.35 mm, the particle size of the ferrosilicon nitride is 0.084-0.095 mm, the particle size of the silicon carbide is 0.071-0.083 mm, the particle size of the mesoporous alumina is 0.65-0.74 mm, and the particle size of the NS-FH composite sintering aid is 0.003-0.005 mm.
[0014] Furthermore, in S1, the specific operation of stirring is: at 45-48°C, the stirring speed of the stirrer is 620-640r / min, and the stirring time is 3-5min.
[0015] Furthermore, in S2, the specific operation of stirring is: at 45-48°C, the stirring speed of the stirrer is 830-850r / min, and the stirring time is 22-24min.
[0016] This application has the following beneficial effects: 1. The raw material components of the environmentally friendly waterless mud of the present invention include mesoporous alumina and a binder glucose. Mesoporous alumina has a high specific surface area and a unique pore structure. On the one hand, mesoporous alumina can adsorb and fix glucose molecules, providing more and more reliable active sites for subsequent reactions, thereby promoting the bonding strength and reliability with other raw materials, and jointly promoting the improvement of the bonding strength / mechanical properties (compressive strength) of the cannon mud; on the other hand, mesoporous alumina can also adsorb the gas produced by glucose under high temperature reaction, and reduce the escape channel of gas (such as water, volatiles, etc.), thereby reducing the apparent porosity, and jointly promoting the densification and structural stability of the cannon mud. There is a synergistic effect between mesoporous alumina and glucose, which can synergistically reduce the apparent porosity of the waterless cannon mud, and synergistically improve the compressive strength of the waterless cannon mud.
[0017] 2. Mesoporous alumina can also effectively adsorb and fix impurity ions in slag iron, thereby reducing the erosion of slag iron on taphole mud; at the same time, the skeleton structure of mesoporous alumina can enhance the strength of taphole mud and resist the erosion of slag iron at high temperature. During the high-temperature sintering process, mesoporous alumina can also react chemically with other raw materials to form stable compound phases, such as mullite, etc. The formation of these compound phases also helps to improve the sintering density and high-temperature strength of taphole mud, improve its volume stability, and thus reduce cracking and peeling caused by temperature changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 , a comparative trend chart of the apparent porosity and high temperature compressive strength test data of the anhydrous cannon muds prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0019] The present application is further described in detail below in conjunction with embodiments.
[0020] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0021] Example 1: (1) Preparation of mesoporous alumina, the preparation method is as follows: A1. Weigh 18.2 g of template CTAB, add it into a three-necked flask filled with 150 mL of deionized water, and stir. The specific operation of stirring is to stir at a constant speed of 210 r / min at 35° C. for 35 min to dissolve the template CTAB in the deionized water to obtain a first solution.
[0022] A2, weigh 120.75g aluminum chloride, add 100mL deionized water to dissolve it, and obtain a second solution. Specifically, put 120.75g aluminum chloride into 100mL deionized water, and stir at a constant speed of 250r / min for 10min. The second solution is added dropwise to the first solution obtained in A1 to obtain a first mixed solution.
[0023] A3, weigh 22.5g urea, add 50mL deionized water to dissolve it, and obtain a third solution. Specifically, put 22.5g urea into 50mL deionized water, and stir at a constant speed of 250r / min for 10min. The third solution is added dropwise to the first mixed solution obtained in A2 to obtain a second mixed solution.
[0024] A4, stirring the second mixed solution obtained in A3, the specific operation of stirring is to stir at a constant speed of 210r / min at 72°C for 24h; then drying, the specific operation of drying is to dry in a drying oven at 62°C for 2h; the obtained solid is ground and put into a muffle furnace, and roasted in an air atmosphere, the roasting process includes two stages, the first stage is to heat up to 400°C at a heating rate of 2°C / min and keep for 3h; the second stage is to heat up to 600°C at a heating rate of 1°C / min and keep for 4h; after the roasting is completed, mesoporous alumina is obtained. The particle size of the mesoporous alumina is 0.65-0.74mm.
[0025] Among them, the template agent CTAB (99%) was purchased from Shandong Lvying Chemical Technology Co., Ltd. Aluminum chloride is crystalline aluminum chloride (MYL-B1 type), which was purchased from Nantong Chenlong Chemical Co., Ltd. Urea was purchased from Suzhou Weifei Environmental Protection Chemical Co., Ltd.
[0026] (2) A method for preparing environmentally friendly anhydrous taphole mud, comprising the following steps: S1. Add 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite, 11 parts of NS-FH composite sintering aid and 7 parts of mesoporous alumina into a mixer by weight, and stir. The specific operation of stirring is at 46°C, the stirring speed of the mixer is 630r / min, and the stirring time is 4min to obtain a first mixture.
[0027] Among them, bauxite is composed of coarse bauxite and fine bauxite, the particle size of coarse bauxite is 3-5mm, the particle size of fine bauxite is 0.1-1.1mm, and the mass ratio of coarse bauxite to fine bauxite is 1:1.5. Bauxite is purchased from Lingshou County Quanfeng Mineral Products Processing Plant.
[0028] NS-FH composite sintering aid is prepared by mixing MgO, ZrO2, YbF3 and ZrSi2, and the mass ratio of MgO, ZrO2, YbF3 and ZrSi2 is 2:1:0.7:0.8. ZrO2 (99%) was purchased from Henan Jiachuang Chemical Technology Co., Ltd. MgO (99.999%), YbF3 (99.9%) and ZrSi2 (99%) were all purchased from Hebei Lifu Optoelectronic Technology Co., Ltd.
[0029] The particle size of brown corundum is 0.27-0.35mm, the particle size of clay is 0.074-0.085mm, the particle size of kyanite is 0.24-0.35mm, the particle size of ferrosilicon nitride is 0.084-0.095mm, the particle size of silicon carbide is 0.071-0.083mm, and the particle size of sericite is 0.066-0.074mm. Brown corundum is purchased from Henan Youji Environmental Protection Technology Co., Ltd. Clay is purchased from Gongyi Xuchen Refractory Co., Ltd., model 01, specification 325 mesh. Kyanite is purchased from Lingshou County Pengxia Furnace Lining Material Processing Plant. Ferrosilicon nitride is purchased from Anyang Dingxing Metallurgical Refractory Co., Ltd. Silicon carbide is purchased from Henan Dongli New Materials Co., Ltd. Sericite is purchased from Lingshou County Shengya Mineral Products Co., Ltd.
[0030] S2. According to the same standard weight proportions, 14 parts of a binder are added to the first mixture obtained in S1, and stirring is continued. The specific stirring operation is at 46° C., a stirring speed of 840 r / min, and a stirring time of 23 min to obtain a second mixture.
[0031] The binder includes glucose and glycerol, and the mass ratio of the two is 3.5:1. Glucose (industrial grade) is purchased from Suzhou Tenghao Chemical Technology Co., Ltd. Glycerol (industrial grade) is purchased from Guangzhou Changlong Chemical Co., Ltd.
[0032] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0033] Example 2: The difference between this example and Example 1 is that: (1) mesoporous alumina is prepared by the following method: A1. Weigh 18.2 g of template CTAB, add it into a three-necked flask filled with 150 mL of deionized water, and stir. The specific operation of stirring is to stir at a constant speed of 220 r / min at 38° C. for 35 min to dissolve the template CTAB in the deionized water to obtain a first solution.
[0034] A2, weigh 120.75g aluminum chloride, add 100mL deionized water to dissolve it, and obtain a second solution. Specifically, put 120.75g aluminum chloride into 100mL deionized water, and stir at a constant speed of 250r / min for 10min. The second solution is added dropwise to the first solution obtained in A1 to obtain a first mixed solution.
[0035] A3, weigh 22.5g urea, add 50mL deionized water to dissolve it, and obtain a third solution. Specifically, put 22.5g urea into 50mL deionized water, and stir at a constant speed of 250r / min for 10min. The third solution is added dropwise to the first mixed solution obtained in A2 to obtain a second mixed solution.
[0036] A4. The second mixed liquid obtained in A3 is stirred at a temperature of 73°C and a stirring speed of 220 r / min for 26 hours. The mixed liquid is then dried in a drying oven at 65°C for 3 hours. The obtained solid is ground and placed in a muffle furnace, and calcined in an air atmosphere. The calcination process includes two stages. In the first stage, the temperature is increased to 400°C at a heating rate of 4°C / min and maintained for 4 hours. In the second stage, the temperature is increased to 600°C at a heating rate of 2°C / min and maintained for 5 hours. After the calcination is completed, mesoporous alumina is obtained.
[0037] Example 3: The difference between this example and Example 1 is that: (2) A method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 28 parts of brown corundum, 35 parts of bauxite, 11 parts of clay, 5 parts of kyanite, 7 parts of ferrosilicon nitride, 14 parts of silicon carbide, 9 parts of sericite, 10 parts of NS-FH composite sintering aid and 6 parts of mesoporous alumina into a mixer by weight, and stir. The specific operation of stirring is at 45°C, the stirring speed of the mixer is 620r / min, and the stirring time is 3min to obtain a first mixture.
[0038] The bauxite consists of coarse bauxite and fine bauxite, the particle size of the coarse bauxite is 3-5 mm, the particle size of the fine bauxite is 0.1-1.1 mm, and the mass ratio of the coarse bauxite to the fine bauxite is 1:1.
[0039] S2. According to the same standard weight parts, 12 parts of binder are added to the first mixture obtained in S1, and stirring is continued. The specific operation of stirring is 45°C, the stirring speed is 830r / min, and the stirring time is 22min to obtain a second mixture. The binder includes glucose and glycerol, and the mass ratio of the two is 3:1.
[0040] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0041] Example 4: The difference between this example and Example 1 is that: (2) A method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 35 parts of brown corundum, 40 parts of bauxite, 15 parts of clay, 8 parts of kyanite, 10 parts of ferrosilicon nitride, 20 parts of silicon carbide, 13 parts of sericite, 12 parts of NS-FH composite sintering aid and 8 parts of mesoporous alumina into a mixer by weight, and stir. The specific operation of stirring is at 48° C., the stirring speed of the mixer is 640 r / min, and the stirring time is 5 min to obtain a first mixture.
[0042] The bauxite is composed of coarse bauxite and fine bauxite, the particle size of the coarse bauxite is 3-5 mm, the particle size of the fine bauxite is 0.1-1.1 mm, and the mass ratio of the coarse bauxite to the fine bauxite is 1:2.
[0043] S2. According to the same standard weight parts, 16 parts of binder are added to the first mixture obtained in S1, and stirring is continued. The specific operation of stirring is 48°C, the stirring speed is 850r / min, and the stirring time is 24min to obtain a second mixture. The binder includes glucose and glycerol, and the mass ratio of the two is 4:1.
[0044] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0045] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of environmentally friendly anhydrous cannon mud, mesoporous alumina is deleted and the binder is tar.
[0046] Specifically, a method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite and 11 parts of NS-FH composite sintering aid into a mixer by weight, and stir. The specific operation of stirring is at 46°C, the stirring speed of the mixer is 630r / min, and the stirring time is 4min to obtain a first mixture.
[0047] S2. According to the same standard weight parts, 14 parts of binder are added to the first mixture obtained in S1, and stirring is continued. The specific stirring operation is 46°C, the stirring speed is 840r / min, and the stirring time is 23min to obtain a second mixture. The binder is tar. The tar is purchased from Dongguang County Jinda Chemical Co., Ltd.
[0048] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0049] Comparative Example 2: The difference between this comparative example and Example 1 is that mesoporous alumina is deleted in the preparation of environmentally friendly anhydrous cannon mud.
[0050] Specifically, a method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite and 11 parts of NS-FH composite sintering aid into a mixer by weight, and stir. The specific operation of stirring is at 46°C, the stirring speed of the mixer is 630r / min, and the stirring time is 4min to obtain a first mixture.
[0051] S2. According to the same standard weight parts, 14 parts of binder are added to the first mixture obtained in S1, and stirring is continued. The specific stirring operation is 46°C, the stirring speed is 840r / min, and the stirring time is 23min to obtain a second mixture. The binder includes glucose and glycerol, and the mass ratio of the two is 3.5:1.
[0052] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0053] Comparative Example 3: The difference between this comparative example and Example 1 is that in the preparation of environmentally friendly anhydrous cannon mud, mesoporous alumina is replaced by alumina, and the binder is tar.
[0054] Specifically, a method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. By weight, 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite, 11 parts of NS-FH composite sintering aid and 7 parts of alumina were added into a mixer and stirred. The specific stirring operation was at 46°C, the mixer speed was 630r / min, and the stirring time was 4min to obtain a first mixed material. Alumina (200 mesh) was purchased from Guangzhou Changyu Chemical Co., Ltd.
[0055] S2. According to the same standard weight parts, 14 parts of a binder are added to the first mixture obtained in S1, and the stirring is continued. The specific stirring operation is 46° C., the stirring speed is 840 r / min, and the stirring time is 23 min to obtain a second mixture. The binder is tar.
[0056] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0057] Comparative Example 4: The difference between this comparative example and Example 1 is that in the preparation of environmentally friendly anhydrous cannon mud, mesoporous alumina is replaced by alumina.
[0058] Specifically, a method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite, 11 parts of NS-FH composite sintering aid and 7 parts of alumina into a mixer by weight, and stir. The specific operation of stirring is at 46°C, the stirring speed of the mixer is 630r / min, and the stirring time is 4min to obtain a first mixture.
[0059] S2. According to the same standard weight parts, 14 parts of binder are added to the first mixture obtained in S1, and stirring is continued. The specific stirring operation is 46°C, the stirring speed is 840r / min, and the stirring time is 23min to obtain a second mixture. The binder includes glucose and glycerol, and the mass ratio of the two is 3.5:1.
[0060] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0061] Comparative Example 5: The difference between this comparative example and Example 1 is that in the preparation of environmentally friendly anhydrous cannon mud, the binder is tar.
[0062] Specifically, a method for preparing environmentally friendly anhydrous taphole mud comprises the following steps: S1. Add 32 parts of brown corundum, 38 parts of bauxite, 13 parts of clay, 6 parts of kyanite, 8 parts of ferrosilicon nitride, 16 parts of silicon carbide, 11 parts of sericite, 11 parts of NS-FH composite sintering aid and 7 parts of mesoporous alumina into a mixer by weight, and stir. The specific operation of stirring is at 46°C, the stirring speed of the mixer is 630r / min, and the stirring time is 4min to obtain a first mixture.
[0063] S2. According to the same standard weight parts, 14 parts of a binder are added to the first mixture obtained in S1, and the stirring is continued. The specific stirring operation is 46° C., the stirring speed is 840 r / min, and the stirring time is 23 min to obtain a second mixture. The binder is tar.
[0064] S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
[0065] Test example: Anhydrous taphole mud was prepared by Example 1 to Example 4 and Comparative Example 1 to Comparative Example 5.
[0066] Test items and method basis: 1. Apparent porosity: Bake the anhydrous taphole mud (test object) to about 80℃, then divide it into small pieces the size of fingers, fill it into a triple mold of 40mm*40mm*160mm, pay attention to the four corners, and then knock it with a wooden hammer to make it tightly filled; after the strip sample is cooled and hardened, take out the strip sample, put it into an iron box (the size of the iron box is slightly larger than the size of the strip sample), put it into an oven for insulation at 450℃ for 5h; sinter the heat-treated strip sample in an electric furnace and keep it at 1350℃ for 3h; finally, test the apparent porosity in accordance with GB / T 2997-2000.
[0067] 2. High temperature compressive strength: refer to the determination method in YB / T 5115-2014. The size of the sample (test object) is 114mm*114mm*65mm, and the measurement conditions are 1350℃*3h.
[0068] Test results: See Table 1.
[0069]
[0070] Result analysis: Analyze Example 1-Example 4 and combine the data in Table 1 and Figure 1 It can be seen that the apparent porosity test data of the environmentally friendly water-free mud prepared by the present invention is as low as below 24.2%, and the high-temperature compressive strength is as high as above 28.1 MPa.
[0071] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1 By comparing Comparative Example 1 and Comparative Example 2, it can be seen that compared with Comparative Example 1 (the binder is tar), the apparent porosity test data of the anhydrous cannon mud obtained in Comparative Example 2 (the binder is glucose and glycerol) increased from 25.3% (Comparative Example 1) to 28.8%, and the high temperature compressive strength test data decreased from 26.4MPa (Comparative Example 1) to 23.5MPa. This shows that in terms of binder selection, directly replacing tar with glucose is more environmentally friendly, but it will lead to an increase in the porosity of the anhydrous cannon mud and a decrease in the high temperature compressive strength, which has a negative impact on the performance and use effect.
[0072] By comparing Comparative Example 1 and Comparative Example 3, it can be seen that compared with Comparative Example 1 (the binder is tar), alumina is added to the raw material components of Comparative Example 3, and the test data of the apparent porosity of the anhydrous cannon mud obtained in Comparative Example 3 is 25.0%, which is very close to 25.3% of Comparative Example 1; at the same time, the high temperature compressive strength test data of the anhydrous cannon mud obtained in Comparative Example 3 is 27.7MPa, which is significantly greater than 26.4MPa of Comparative Example 1. It shows that when the binder is tar, adding alumina to the raw material components can improve the high temperature compressive strength of the anhydrous cannon mud, but has little effect on the apparent porosity.
[0073] By comparing Comparative Example 2 and Comparative Example 4, it can be seen that compared with Comparative Example 2 (the binder is glucose and glycerol), alumina is added to the raw material components of Comparative Example 4, and the test data of the apparent porosity of the anhydrous cannon mud obtained in Comparative Example 4 is 28.3%, which is very close to 28.8% of Comparative Example 2; at the same time, the high temperature compressive strength test data of the anhydrous cannon mud obtained in Comparative Example 4 is 24.3MPa, which is significantly greater than 23.5MPa of Comparative Example 2. It shows that when the binder is glucose, adding alumina to the raw material components can also improve the high temperature compressive strength of the anhydrous cannon mud, but has little effect on the apparent porosity.
[0074] By comparing Comparative Example 3 and Comparative Example 5, it can be seen that compared with the alumina in the raw material component of Comparative Example 3 (the binder is tar), the raw material component of Comparative Example 5 (the binder is tar) contains an equal amount of mesoporous alumina. As a result, the test data of the apparent porosity of the anhydrous cannon mud obtained in Comparative Example 5 is 26.5%, which is significantly greater than 25.0% of Comparative Example 3; at the same time, the high temperature compressive strength test data of the anhydrous cannon mud obtained in Comparative Example 5 is 27.1MPa, which is significantly less than 27.7MPa of Comparative Example 3. It shows that when the binder is tar, replacing the alumina in the raw material component with mesoporous alumina will increase the apparent porosity of the anhydrous cannon mud and reduce the high temperature compressive strength.
[0075] By comparing Comparative Example 4 with Example 1, it can be seen that compared with the alumina in the raw material components of Comparative Example 4 (the binder is glucose and glycerol), the raw material components of Example 1 (the binder is glucose and glycerol) contain an equal amount of mesoporous alumina. As a result, the test data of the apparent porosity of the anhydrous cannon mud prepared in Example 1 is 24.2%, which is significantly less than 28.3% of Comparative Example 4; at the same time, the high-temperature compressive strength test data of the anhydrous cannon mud prepared in Example 1 is 28.3MPa, which is significantly greater than 24.3MPa of Comparative Example 4. This shows that when the binder is glucose, replacing the alumina in the raw material components with mesoporous alumina can significantly reduce the apparent porosity of the anhydrous cannon mud and significantly improve the high-temperature compressive strength.
[0076] In summary, there is a synergistic effect between mesoporous alumina and the binder glucose, which can synergistically reduce the apparent porosity of the anhydrous cannon clay and synergistically improve the high-temperature compressive strength of the anhydrous cannon clay.
[0077] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0078] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing environmentally friendly anhydrous taphole mud, characterized in that: The steps include: S1. Add 28-35 parts of brown corundum, 35-40 parts of bauxite, 11-15 parts of clay, 5-8 parts of kyanite, 7-10 parts of ferrosilicon nitride, 14-20 parts of silicon carbide, 9-13 parts of sericite, 10-12 parts of NS-FH composite sintering aid and 6-8 parts of mesoporous alumina into a mixer, stir to obtain a first mixture; S2, adding 12-16 parts of a binder by weight to the first mixture obtained in S1, continuing to stir and mix, to obtain a second mixture; the binder comprises glucose and glycerol, and the mass ratio of the two is (3-4):1; S3. The second mixed material obtained in S2 is squeezed out from the discharge port of the mixer to obtain environmentally friendly anhydrous taphole mud.
2. The method for preparing environmentally friendly anhydrous taphole mud according to claim 1, characterized in that: The preparation method of the mesoporous alumina is as follows: A1. Weigh 18.2 g of template agent CTAB, add it into a three-necked flask filled with 150 mL of deionized water, stir and dissolve to obtain a first solution; A2, weigh 120.75 g of aluminum chloride, add it into 100 mL of deionized water to dissolve it, to obtain a second solution, and add the second solution dropwise into the first solution obtained in A1 to obtain a first mixed solution; A3, weigh 22.5 g of urea, add it into 50 mL of deionized water to dissolve it, to obtain a third solution, and add the third solution dropwise into the first mixed solution obtained in A2, to obtain a second mixed solution; A4. The second mixed liquid obtained in A3 is stirred and then dried to obtain a solid which is ground and placed in a muffle furnace and calcined in an air atmosphere to obtain mesoporous alumina.
3. The method for preparing environmentally friendly anhydrous taphole mud according to claim 2, characterized in that: In A1, the specific stirring operation is: stirring at a temperature of 35-38° C. and a stirring speed of 200-220 r / min for 33-35 min.
4. The method for preparing environmentally friendly anhydrous taphole mud according to claim 2, characterized in that: In A4, the specific stirring operation is: stirring at a temperature of 70-73° C. and a stirring speed of 200-220 r / min for 24-26 hours.
5. The method for preparing environmentally friendly anhydrous taphole mud according to claim 2, characterized in that: In A4, the specific operation of drying is: drying in a drying oven at 60-65°C for 2-3 hours.
6. The method for preparing environmentally friendly anhydrous taphole mud according to claim 2, characterized in that: In A4, the calcination process includes two stages. In the first stage, the temperature is raised to 400°C at a rate of 2-4°C / min and maintained for 3-4 hours. In the second stage, the temperature is raised to 600°C at a rate of 1-2°C / min and maintained for 4-5 hours.
7. The method for preparing environmentally friendly anhydrous taphole mud according to claim 1, characterized in that: The bauxite consists of coarse bauxite and fine bauxite, the particle size of the coarse bauxite is 3-5 mm, the particle size of the fine bauxite is 0.1-1.1 mm, and the mass ratio of the coarse bauxite to the fine bauxite is 1:(1-2).
8. The method for preparing environmentally friendly anhydrous taphole mud according to claim 1, characterized in that: The particle size of the sericite is 0.066-0.074 mm, the particle size of the brown corundum is 0.27-0.35 mm, the particle size of the clay is 0.074-0.085 mm, the particle size of the kyanite is 0.24-0.35 mm, the particle size of the ferrosilicon nitride is 0.084-0.095 mm, the particle size of the silicon carbide is 0.071-0.083 mm, the particle size of the mesoporous alumina is 0.65-0.74 mm, and the particle size of the NS-FH composite sintering aid is 0.003-0.005 mm.
9. The method for preparing environmentally friendly anhydrous taphole mud according to claim 1, characterized in that: In S1, the specific operation of stirring is: at 45-48°C, the stirring speed of the stirrer is 620-640 r / min, and the stirring time is 3-5 min.
10. The method for preparing environmentally friendly anhydrous taphole mud according to claim 1, characterized in that: In S2, the specific operation of stirring is: at 45-48°C, the stirring speed of the stirrer is 830-850r / min, and the stirring time is 22-24min.
Citation Information
Patent Citations
Bonding agent, stemming including bonding agent and preparation method of stemming
CN105110674A
High-performance non-sintered sliding plate joint material and preparation method thereof
CN105541310A
Novel homogenized stemming
CN106242538A
High-strength environment-friendly stemming material
CN106348772A
High-silicon carbide-containing castable refractory
JP2002020177A